2009
DOI: 10.1007/s10450-009-9184-7
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mesoporous niobosilicates synthesized using F127 triblock copolymer

Abstract: A detailed characterization of cage-like mesoporous SBA-16 niobosilicate with tailored features of the structure is reported. The materials were synthesized in a EO 106 PO 70 EO 106 (F127)-water system under acidic conditions and the pore diameters were tuned by varying the hydrothermal treatment temperature and time. The effects of the synthesis parameters on the structural/textural properties of the cubic Im3m niobosilicates have been investigated systematically. We show that the total pore volume, pore diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Different types of mesoporous materials containing niobium have been prepared and tested in oxidation reactions with H 2 O 2 (Nowak et al, 2003 ; Nowak and Ziolek, 2005 ; Somma and Strukul, 2006 ; Feliczak-Guzik et al, 2009 ; Gallo et al, 2013 ; Tiozzo et al, 2014 ; Ivanchikova et al, 2015 , 2017 ; Ramanathan et al, 2015 ; Thornburg et al, 2015 ; Dworakowska et al, 2017 ; Thornburg and Notestein, 2017 ).…”
Section: Catalysis On Niobium-containing Mesoporous Silicatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Different types of mesoporous materials containing niobium have been prepared and tested in oxidation reactions with H 2 O 2 (Nowak et al, 2003 ; Nowak and Ziolek, 2005 ; Somma and Strukul, 2006 ; Feliczak-Guzik et al, 2009 ; Gallo et al, 2013 ; Tiozzo et al, 2014 ; Ivanchikova et al, 2015 , 2017 ; Ramanathan et al, 2015 ; Thornburg et al, 2015 ; Dworakowska et al, 2017 ; Thornburg and Notestein, 2017 ).…”
Section: Catalysis On Niobium-containing Mesoporous Silicatesmentioning
confidence: 99%
“…Nowak et al described the selective oxidation of terpenes and terpenoids, such as geraniol, limonene, α-terpineol using H 2 O 2 as an oxidant over NbMSU-X-catalysts (Feliczak-Guzik et al, 2009 ), which are characterized by a 3D interconnecting network of “worm-like” pores (Feliczak and Nowak, 2007 ). The oxidation of terpenes/terpenoids was performed in glass batch reactor upon dynamic stirring at 313 K for 23 h. Products of reaction were evaluated by GC and GC-MS.…”
Section: Catalysis On Niobium-containing Mesoporous Silicatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-SBA-16, Ti-SBA-16, V-SBA-16, Fe-SBA-16 and Nb-SBA-16 mesoporous silicas with a cubic Im3m structure have been successfully synthesized using silica precursors and a triblock copolymer under acidic condition [44,75–80]. …”
Section: Applicationsmentioning
confidence: 99%
“…It was found that pore volume, pore diameter, and micro-/mesopores ratio can be controlled very efficiently by changing the synthesis parameters [80]. …”
Section: Applicationsmentioning
confidence: 99%